İslâm Hâkimiyetine (II./VIII. Asır) Kadarki Dönemde Soğd Havzasının İktisadî ve Sosyokültürel Dinamikleri - (:unkn) unknown (My University, 2014)
0

Sughd Region (Sogdia), which is located in the area known as Māwarānnahr (Transoxania), between the Amu Darya and Syr Darya rivers, was an important center for Islamic culture and civilization. The residents of Sughd, due to the fact that they had very fertile land and occupied a very influential position in the commerce on the Silk Road, had developed a high culture many centuries before the birth of Islam. The components of this superior culture and civilization also effected nearby people and regions. A significant number of schools of belief and thought which had been persecuted in other regions sought refuge in Sughd and this became a place in which they found the opportunity to spread. The impor- tance of the region increased after it was conquered by Muslims, and with the ef- fect of the high culture that the region had had before the advent of Islam the area became a center of attraction for merchants, scientists and men of religion from every part of the Islamic world. As a result, Sughd occupied a unique and respected position in Māwarānnahr and even in Central Asia not only from political and economic aspects, but also from a cultural perspective. This article will investigate what kind of cultural, social and civilizational infrastructure existed in the region before the religion of Islam entered the region in order to identify how it managed to possess these superior qualities
Keywords: Din Bilimi